Dynamic monitoring of service members to quantify blast exposure levels during combat training using BlackBox Biometrics Blast Gauges: explosive breaching, shoulder-fired weapons, artillery, mortars, and 0.50 caliber guns - Wiri, Suthee; Massow, Todd; Reid, James; Whitty, Joshua; Dunbar, Cyrus; Graves, Wallace; Gonzales, Andrea; Ortley, David; Longwell, Jasmyne; Needham, Charles E.; Ziegle, Alex; Phan, Virginia; et al. (Frontiers in Neurology, 2023)
CONQUER is a pilot blast monitoring program that monitors, quantifies, and reports to military units the training-related blast overpressure exposure of their service members. Overpressure exposure data are collected using the BlackBox Biometrics (B3) Blast Gauge System (BGS, generation 7) sensors mounted on the body during training. To date, the CONQUER program has recorded 450,000 gauge triggers on monitored service members. The subset of data presented here has been collected from 202 service members undergoing training with explosive breaching charges, shoulder-fired weapons, artillery, mortars, and 0.50 caliber guns. Over 12,000 waveforms were recorded by the sensors worn by these subjects. A maximum peak overpressure of 90.3 kPa (13.1 psi) was recorded during shoulder-fired weapon training. The largest overpressure impulse (a measure of blast energy) was 82.0 kPa-ms (11.9 psi-ms) and it was recorded during explosive breaching with a large wall charge. Operators of 0.50 caliber machine guns have the lowest peak overpressure impulse (as low as 0.62 kPa-ms or 0.09 psi-ms) of the blast sources considered. The data provides information on the accumulation of blast overpressure on service members over an extended period of time. The cumulative peak overpressure, peak overpressure impulse, or timing between exposures is all available in the exposure data.